Innovations in teaching university: emerging opportunities - Daniele Simões Borges; Gionara Tauchen (Universidade Federal de Santa Maria, 2012)
The present abstract understands that the university, into the current society, can build environments that indulge the development of the culture the creation and the innovation. Therefore we aim to understand the processes of induction of the university teaching, as well as the didactic-pedagogic activities proposed in the Teaching Projects of a university from the south of Rio Grande do Sul. The research is naturally qualitative and documentary, it has been done through Content Analysis (Franco, 2008; Bardin, 1977). In the study were analyzed 163 projects, being highlighted three major points of innovative teaching practices: a) practical activities, including field exploring, use of lab and practical tasks in the classroom; b) new technologies, including the use of Blogs, MSN, AVA, robotics, moodle, modeling, videos, recordings, forums, and diaries e c) innovative methodologies, referring to learning projects, problem solving, workshops, work groups, articulation between teaching, research and extension and daily evaluation. We consider that the changes in the teaching perceptions, due to self-formative processes and the induction of institutional policy to avoid retention and evasion, as well as the innovation, has been contributed to the improvement of the learning and teaching in the university. We emphasize, also, that the innovation in the teaching can come from different levels, activities and manners, expressing different epistemological and paradigmatic basis. Therefore, it needs to be considered as activity in a particular context, coming from a collective and institutional nature.